Would Antarctic Marine Benthos Survive Alien Species Invasions? What Chemical Ecology May Tell Us - Conxita Avila; Xavier Buñuel; Francesc Carmona; Albert Cotado; Oriol Sacristán-Soriano; Carlos Angulo-Preckler (Marine Drugs, 2022)
Many Antarctic marine benthic macroinvertebrates are chemically protected against predation by marine natural products of different types. Antarctic potential predators mostly include sea stars (macropredators) and amphipod crustaceans (micropredators) living in the same areas (sympatric). Recently, alien species (allopatric) have been reported to reach the Antarctic coasts, while deep-water crabs are suggested to be more often present in shallower waters. We decided to investigate the effect of the chemical defenses of 29 representative Antarctic marine benthic macroinvertebrates from seven different phyla against predation by using non-native allopatric generalist predators as a proxy for potential alien species. The Antarctic species tested included 14 Porifera, two Cnidaria, two Annelida, one Nemertea, two Bryozooa, three Echinodermata, and five Chordata (Tunicata). Most of these Antarctic marine benthic macroinvertebrates were chemically protected against an allopatric generalist amphipod but not against an allopatric generalist crab from temperate waters. Therefore, both a possible recolonization of large crabs from deep waters or an invasion of non-native generalist crab species could potentially alter the fundamental nature of these communities forever since chemical defenses would not be effective against them. This, together with the increasing temperatures that elevate the probability of alien species surviving, is a huge threat to Antarctic marine benthos.